O ensino de Espanhol por meio do protótipo didático digital: uma experiência com os letramentos transmídia - Lemos, Rodolfo Aparecido (Universidade Federal de São Carlos, 2024)
The social isolation resulting from the COVID-19 pandemic has driven people to migrate to the digital environment, consolidating it as a predominant way of life. Social interactions occur mainly on networks, where people consume and produce content in various formats, genres, and languages. This phenomenon impacted education significantly, leading schools and universities to adapt their teaching schedules to the digital landscape and seek support from New Digital Information and Communication Technologies (NDTICs) and Digital Learning Objects (DLOs). In the specific context of teaching Spanish as a foreign language (E/LE), current classes highlight challenges students face, such as under-utilization of communicative competence in the target language, lack of criticality, and inefficiency in selecting reliable sources on the web. Given this scenario, it has become essential to devise a digital and interactive teaching plan that integrates digital discursive genres with the communicative and linguistic content usual in the Spanish language's multi-semiotic and multimedia cultural products, adopting transmedia literacy practices. This approach aims to promote students' ability to use the target language through content management and analysis, sharing, storing, and, most importantly, producing communicative knowledge. In this context, this research organized work according to the cycles of action research, in which the researcher also worked as a teacher of the intermediate Spanish II course at a language institute of a federal university. Throughout the lessons, the researcher developed a digital didactic prototype, using sociocultural products adapted to the Spanish language as DLOs, to expand the communicative and critical skills of the participating students in the target language. The results indicate that transmedia literacy practices led to significant acquisition of critical, linguistic, and communicative skills in Spanish classes. It has broadened students' sociocultural repertoire, as well. The digital prototype seems up-to-date and timely teaching material for the language institute's pedagogical activities. In addition, the results of this research study also present relevant ethnographic data for the scientific community and future studies in the research locus.
The teaching of Spanish through the digital didactic prototype: an experience with transmedia literacies
Keywords: Letramento transmídia; Letramento crítico; Tecnologias digitais de informação e comunicação; Multimodalidade; Ubiquidade; Transmedia literacy; Critical literacy; Digital information and communication technologies; Multimodality; Ubiquity; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA